Implementation Patterns of BPNT in Kedungrawan Village Krembung: Pola Implementasi BPNT di Desa Kedungrawan Krembung - Putri, Rika Rikhmalia; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Poverty remains a persistent social issue in developing countries, including Indonesia. Specific Background: The Non-Cash Food Assistance Program (BPNT) was designed as a food subsidy distributed electronically to beneficiary households through e-warong. Knowledge Gap: Several implementation problems such as mistargeted beneficiaries, zero balances, and delayed distribution are still found at the village level. Aim: This study aims to analyze the implementation of the BPNT program in Kedungrawan Village, Krembung District. Methods: This research uses a descriptive qualitative approach with data collected through interviews, observations, and documentation involving village officials, BPNT facilitators, and beneficiaries. Results: The findings indicate that communication, human resources, disposition, and bureaucratic structure generally operate according to established procedures. However, obstacles remain in targeting accuracy, zero balances in beneficiary accounts, and data updates in the DTKS system. Novelty: This study highlights local-level implementation dynamics of BPNT using Edward III’s policy implementation framework. Implications: The findings provide input for improving data validation, monitoring, and coordination to ensure more accurate and sustainable food assistance distribution. Keywords: BPNT Program, Policy Implementation, Poverty Alleviation, Social Assistance, Rural Welfare Highlights: Community-level BPNT distribution follows formal operational procedures. Data updating and targeting accuracy remain major implementation challenges. Human resource capacity supports program continuity.